2018
DOI: 10.1051/0004-6361/201832932
|View full text |Cite
|
Sign up to set email alerts
|

Correcting for peculiar velocities of Type Ia supernovae in clusters of galaxies

Abstract: Context. Type Ia Supernovae (SNe Ia) are widely used to measure the expansion of the Universe. To perform such measurements the luminosity and cosmological redshift (z) of the SNe Ia have to be determined. The uncertainty on z includes an unknown peculiar velocity, which can be very large for SNe Ia in the virialized cores of massive clusters. Aims. We determine which SNe Ia exploded in galaxy clusters. We then study how the correction for peculiar velocities of host galaxies inside the clusters improves the H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 113 publications
0
7
0
2
Order By: Relevance
“…Using 145 SNe Ia from the Nearby Supernova Factory 11 candidates for membership in clusters were found. It was shown that for SNe Ia inside galaxy clusters the dispersion around the Hubble diagram when peculiar velocities are taken into account is smaller in comparison with a case without peculiar velocity correction, with a wRMS = 0.130 ± 0.038 mag instead of wRMS = 0.137 ± 0.036 mag [2]. However, this study was done with nearby sample of supernovae.…”
Section: Pos(apcs2018)050mentioning
confidence: 86%
See 3 more Smart Citations
“…Using 145 SNe Ia from the Nearby Supernova Factory 11 candidates for membership in clusters were found. It was shown that for SNe Ia inside galaxy clusters the dispersion around the Hubble diagram when peculiar velocities are taken into account is smaller in comparison with a case without peculiar velocity correction, with a wRMS = 0.130 ± 0.038 mag instead of wRMS = 0.137 ± 0.036 mag [2]. However, this study was done with nearby sample of supernovae.…”
Section: Pos(apcs2018)050mentioning
confidence: 86%
“…If we transform this dispersion into a magnitude error, we will see that for lowredshift region (z < 0.05) this error is several times more than the one corresponding to 150 km s −1 and 300 km s −1 , moreover, it is two times larger than the intrinsic dispersion of SNe Ia around the Hubble diagram (0.11 mag, see fig. 2 in [2]). It means that standard methods for peculiar velocity correction do not work for the galaxies inside the clusters and another, more accurate method has to be developed.…”
Section: Pos(apcs2018)050mentioning
confidence: 99%
See 2 more Smart Citations
“…Среди сверхновых Pantheon 297 объектов имеют красное смещение z < 0.15. Для таких СН вклад пекулярных скоростей наиболее значим [1] (рис. 1).…”
unclassified